2014
DOI: 10.1210/jc.2014-2701
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Incidence of Renal Replacement Therapy in People With Type 1 Diabetes Mellitus–A Three Decade Long Prospective Observational Study in the Lainz T1DM Cohort

Abstract: In people with established type 1 diabetes who were observed for almost three decades, the overall mortality was 24% and the incidence of renal replacement therapy was 8.6%, with a 21.8% combined incidence rate of the other hard endpoints in the surviving people. A clear linear relationship between early glycemic control and the later development of end stage renal disease and mortality has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Furthermore, it must be kept in mind that the prognosis of patients with type 1 diabetes and diabetic nephropathy is still poor in developing countries (24). There is strong evidence that better glucose control as well as treatment of hypertension and dyslipidemia decreases the risk of diabetic nephropathy and ESRD in patients with type 1 diabetes (7,(25)(26)(27)(28)(29)(30)(31). The use of multiple insulin injections became more common in the 1990s and was followed by the development of rapid-acting and long-acting insulin regimens, which enabled patients with type 1 diabetes to maintain a more stable blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it must be kept in mind that the prognosis of patients with type 1 diabetes and diabetic nephropathy is still poor in developing countries (24). There is strong evidence that better glucose control as well as treatment of hypertension and dyslipidemia decreases the risk of diabetic nephropathy and ESRD in patients with type 1 diabetes (7,(25)(26)(27)(28)(29)(30)(31). The use of multiple insulin injections became more common in the 1990s and was followed by the development of rapid-acting and long-acting insulin regimens, which enabled patients with type 1 diabetes to maintain a more stable blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard of ESRD was also reported higher in Latinos, Chinese, Japanese and Pacific Islanders [20]. Studies also identified baseline eGFR and albuminuria [14,25,37,41,67,71,75,76], longer duration of diabetes, poor glycaemic control (higher HbA 1c ) [25,31,37,48,53,67,76,78], late onset of diabetes in Type 1 diabetes [51], high blood pressure and use of angiotensinconverting enzyme inhibitors [25,79] increased the risk of ESRD. Lower incidence of ESRD was reported among those with diabetes diagnosed in recent years compared to earlier time intervals [25,29,30,47,64,76].…”
Section: Incidence Of Esrd Among People With Diabetesmentioning
confidence: 99%
“…Several studies reported a higher incidence of ESRD among men than women [25,48,51], but others [47,53,64] reported no significant differences. Incidence of ESRD was higher among African Americans [20,27,29], native people in Canada [77] and Maoris in New Zealand [81] compared with white people (Europids).…”
Section: Incidence Of Esrd Among People With Diabetesmentioning
confidence: 99%
“…2 However, even with HbA 1c < 7.0% the residual risk for cardiovascular and all-cause mortality in patients with T1D remains more than twice that in nondiabetics, 3 with the lowest mortality rates seen with HbA 1c ≤ 6.5%. 4 Unfortunately, despite tremendous advances doi: 10.1111/nyas.14214 5 in the technology available for insulin delivery and glucose monitoring and their use over the past decade, glycemic control has worsened in adults with T1D in the United States receiving specialized diabetes care with currently only 21% achieving the recommended HbA 1c level <7.0%. 5 In addition, 7% reported experiencing a severe hypoglycemic event resulting in seizure or loss-of-consciousness in the prior 3 months, including 11% of those with HbA 1c < 7.0%, 7% of those with HbA 1c in the range 7.0 to <9.0%, and 8% of those with HbA 1c ≥ 9.0% ( Fig.…”
Section: Introductionmentioning
confidence: 99%